Not in vain ; 11th what God hath wrought amongst the Kanakas in Queensland [with appendix, containing, inter aha Report of the Queensland Kanaka Mission for the year 1896-97] (1897)
Contents includes : Queensland Kanaka Mission : Object and principles (revised).
Photocopy. Missing t.p., pages 1-5.
Keywords: Queensland Kanaka Mission; Brethren movement -- missions -- Australia -- history